1988
DOI: 10.1007/bf00844432
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of participation in a worksite stop-smoking contest

Abstract: Smokers employed at Roswell Park Memorial Institute, a cancer hospital and research center located in Buffalo, New York, were offered the opportunity to participate in a quit-smoking contest in which cash prizes were awarded for stopping smoking. Information on the smoking habits and attitudes of employees collected in a survey 3 months before the contest was used to predict the characteristics of smokers associated with contest participation. The same variables were also used to predict cessation among contes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…The data were analyzed using STATA 7.0 and additional software that estimates the error rates of diagnostic tests or measurements when there is no gold standard by applying maximum likelihood estimation methods to latent class models representing the observed data. 7 Descriptive analyses were used to examine the characteristics of the study sample. The normality of the distribution of riskperception scores for each measure was assessed using the Shapiro-Wilks test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data were analyzed using STATA 7.0 and additional software that estimates the error rates of diagnostic tests or measurements when there is no gold standard by applying maximum likelihood estimation methods to latent class models representing the observed data. 7 Descriptive analyses were used to examine the characteristics of the study sample. The normality of the distribution of riskperception scores for each measure was assessed using the Shapiro-Wilks test.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, many studies have assessed risk perception to test models that posit an association between risk perception and health behavior (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Other research assesses risk perception to detect errors and biases in risk judgments (15)(16)(17)(18), to assess the association between risk judgments and emotion (19)(20)(21)(22)(23)(24)(25), and to increase the accuracy of people's risk perceptions (11,(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Cummings et al [10] smokers were placed in a worksite Stop-Smoking Contest in which cash prizes were awarded for quitting smoking. The study showed that onethird of participants managed to stay abstinent after 3 months, indicating that competition and/or monetary gain are strong motivators to stop smoking.…”
Section: -Competitionmentioning
confidence: 99%
“…23,43,53,55,[67][68][69] All of these studies provided incentives for participation. It appears that if incentives are tailored to fit the company and employee culture, they can substantially enhance participation rates.…”
Section: Program Designmentioning
confidence: 99%